The War in Ukraine: Challenges for the Polish Education System - Wawrzyniec Roch Kowalski (The Francis de Sales Scientific Society (TNFS.PL), 2023)
The article takes a closer look at the most relevant issues related to the sudden influx of refugees from Ukraine fleeing from the war to Poland. A significant part of them, according to Polish law, is of an age that is subject to compulsory education or schooling. In view of this, in a short period of time, almost 200 thousand pupils from Ukraine were placed in the units of the Polish education system. The purpose of this article is to present the scale of the problem - statistical data on pupils who are refugees, citizens of Ukraine, the measures taken by the Government of the Republic of Poland and the Ministry of Education and Science that were necessary to meet the considerable challenges, primarily the legal regulations and financial resources allocated from the state budget to provide these measures. According to the reported data, almost 198.3 thousand children and pupils who have arrived from Ukraine since 24 February 2022 (currently more than 182 thousand) are listed in the units of the Polish education system (in pre-school education, primary and secondary schools). Children and pupils - refugees from Ukraine can be found in all 16 provinces, all across Poland, although almost 40% are concentrated in provincial cities, with the highest number in Warsaw - 17 thousand and about 8 thousand in Wrocław and Kraków each. Faced with this situation, a number of ad hoc systemic changes have been introduced and financial resources of around PLN 3 billion have been allocated from the state budget. The war in Ukraine and the exodus caused by it has become a considerable challenge for the Polish education system. Poland, despite the lack of external financial assistance (including from the European Union), opened the doors of its borders, homes and schools from the first days of this military conflict, providing the necessary support to refugees and introducing the necessary systemic changes to enable the absorption of such a large number of children and young people, in a short period of time, in the middle of the school year.